Antibiotic resistance: the challenge from an industry perspective. Issue 2 (March 2009) - Tillotson, Glenn S
Trained in medical microbiology and infectious diseases in the UK, Glenn Tillotson has over 20 years pharmaceutical experience in various areas, including clinical research, marketing, scientific communications, strategic development and global launch programs. Mainly in the field of anti-infectives, Tillotson has been instrumental in the development of ciprofloxacin and moxifloxacin, as well as other drugs in the Bayer portfolio. After leaving Bayer, he worked as a consultant microbiologist and, in 2003, consulted with Genesoft to help with the commercialization and launch of gemifloxacin, leading to the development of Oscient following the merger of Genesoft and Genome Therapeutics. From late 2003 to early 2006, he focused his efforts on the launch of gemifloxacin into US clinical practice, as well as comarketing and business development deals globally. In April 2006, Tillotson joined Replidyne Inc. as Executive Director of Scientific Affairs working on faropenem, REP 8839 and REP 3123. Presently, Tillotson is Head of Medical Affairs at ViroPharma Inc., where he oversees educational, publication and other related activities for Vancocin ®, maribavir and Cinryze™. Most recently, Tillotson was a member of the Scientific Steering Committee for the International Society of Chemotherapy''s Symposium on Clostridium difficile in Leipzig, Germany. Here, he talks with Expert Review of Clinical Pharmacology about the challenge of antibiotic resistance from an industry perspective.